The DnaK Chaperone Uses Different Mechanisms To Promote and Inhibit Replication of Vibrio cholerae Chromosome 2 - Jyoti K. Jha (American Society for Microbiology, 2017)
ABSTRACT Replication of Vibrio cholerae chromosome 2 (Chr2) depends on molecular chaperone DnaK to facilitate binding of the initiator (RctB) to the replication origin. The binding occurs at two kinds of site, 12-mers and 39-mers, which promote and inhibit replication, respectively. Here we show that DnaK employs different mechanisms to enhance the two kinds of binding. We found that mutations in rctB that reduce DnaK binding also reduce 12-mer binding and initiation. The initiation defect is suppressed by second-site mutations that increase 12-mer binding only marginally. Instead, they reduce replication inhibitory mechanisms: RctB dimerization and 39-mer binding. One suppressing change was in a dimerization domain which is folded similarly to the initiator of an iteron plasmid—the presumed progenitor of Chr2. In plasmids, DnaK promotes initiation by reducing dimerization. A different mutation was in the 39-mer binding domain of RctB and inactivated it, indicating an alternative suppression mechanism. Paradoxically, although DnaK increases 39-mer binding, the increase was also achieved by inactivating the DnaK binding site of RctB. This result suggests that the site inhibits the 39-mer binding domain (via autoinhibition) when prevented from binding DnaK. Taken together, our results reveal an important feature of the transition from plasmid to chromosome: the Chr2 initiator retains the plasmid-like dimerization domain and its control by chaperones but uses the chaperones in an unprecedented way to control the inhibitory 39-mer binding. IMPORTANCE The capacity of proteins to undergo remodeling provides opportunities to control their function. However, remodeling remains a poorly understood aspect of the structure-function paradigm due to its dynamic nature. Here we have studied remodeling of the initiator of replication of Vibrio cholerae Chr2 by the molecular chaperone, DnaK. We show that DnaK binds to a site on the Chr2 initiator (RctB) that promotes initiation by reducing the initiator’s propensity to dimerize. Dimerization of the initiator of the putative plasmid progenitor of Chr2 is also reduced by DnaK, which promotes initiation. Paradoxically, the DnaK binding also promotes replication inhibition by reducing an autoinhibitory activity of RctB. In the plasmid-to-chromosome transition, it appears that the initiator has acquired an autoinhibitory activity and along with it a new chaperone activity that apparently helps to control replication inhibition independently of replication promotion.